2022
DOI: 10.1177/03000605221083441
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of a pseudoaneurysm of the posterior inferior pancreaticoduodenal artery as a complication of chronic pancreatitis: a case report

Abstract: A pancreatic pseudoaneurysm is a rare but life-threatening clinical entity. Prompt diagnosis and appropriate treatment are of great clinical importance. We herein present an unusual case of a pseudoaneurysm of the posterior inferior pancreaticoduodenal artery that developed as a complication of chronic pancreatitis. It was detected in a timely manner and successfully treated with minimally invasive endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…Ren et al [ 21 ] reported on their endovascular treatment of 159 patients with visceral artery aneurysms and pseudoaneurysms, with 96.9% of patients successfully treated and a 1.9% mortality rate at 30 days. Similar to our case, Mitrovic et al [ 13 , 14 , 15 ] reported successful endovascular resolution of a posterior inferior pancreaticoduodenal artery pseudoaneurysm using the sandwich technique, in which the pseudoaneurysm inflow and outflow were embolized with coils. Jang et al [ 16 ], on the other hand, embolized the pseudoaneurysm with an N-Butyl-Cyanoacrylate-lipiodol composition.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Ren et al [ 21 ] reported on their endovascular treatment of 159 patients with visceral artery aneurysms and pseudoaneurysms, with 96.9% of patients successfully treated and a 1.9% mortality rate at 30 days. Similar to our case, Mitrovic et al [ 13 , 14 , 15 ] reported successful endovascular resolution of a posterior inferior pancreaticoduodenal artery pseudoaneurysm using the sandwich technique, in which the pseudoaneurysm inflow and outflow were embolized with coils. Jang et al [ 16 ], on the other hand, embolized the pseudoaneurysm with an N-Butyl-Cyanoacrylate-lipiodol composition.…”
supporting
confidence: 85%
“…Arterial aneurysmal dilatation develops as a result of damage to the collagen structure at the arterial wall caused by atherosclerosis or hypertension, and is found with the highest incidence at the level of the abdominal aorta [ 5 , 6 , 7 , 8 , 9 ]. In contrast, arterial pseudoaneurysms are connected with trauma, surgical treatments, or the presence of malignancies, but in the case of the pancreaticoduodenal artery, the main reason is the association with chronic pancreatitis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although it is a rare pathology, it is lethal in the absence of intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 Moreover, three of four patients with abdominal pain were considered to have pancreatitis-related abdominal pain. 3,5,7 Notably, abdominal pain was present in all cases in the ruptured aneurysm group. [10][11][12] In addition, except for one, 11 all patients had severe symptoms, such as sudden or severe abdominal pain.…”
Section: Discussionmentioning
confidence: 90%
“…The US findings in one case 6 were not detailed, but all other cases were depicted as cystic masses with blood flow signals. [2][3][4][5]7 PDAA was diagnosed in three of the cases during pancreatitis follow-up owing to the appearance of a blood flow signal on color Doppler inside a large hypoechoic cystic mass suggestive of a pancreatic pseudocyst or walled-off necrosis. 3,5,7 On the contrary, the size was not noted in all cases in the ruptured aneurysm group.…”
Section: Discussionmentioning
confidence: 99%